Molecular simulation studies of 1, 6 hexamethylenediamine (HMDA) absorption process for co2 capture - Mohamad Hafiz Zulkarnain, Azman (2015)
Carbon dioxide, CO2 capture by absorption with aqueous alkanolamines is considered an important technology for reducing CO2 emissions and global climate changes. The main objective of this work is to study the effect of temperature on intermolecular interaction of 1, 6-Hexamethylenediamine (HMDA) absorption process for CO2 capture by using molecular dynamic (MD) simulation technique. The simulation was performed under condition NVE (200 ps) and NPT (500 ps) ensembles in material studio version 7.1. Two different temperature are used which are 313K and 333K for tertiary system (HMDA + CO2 + water, 1120). in this study, radial distribution function (RDF) and mean square displacement (MSD) are used to analyze intermolecular interaction exist in the system and self diffusion coefficient. According to the results, the possibility interaction or g(r) values of Ow-Hw (hydrogen bond) at 313K and 333K are (1.75 A, 19.75) and (1.75 A, 38.39). Meanwhile, g(r) value for intermolecular interaction of Nhmda-Cco2 (carbamate formation) are (3.75 A, 2.43) and (4.75 A, 2.61) at temperature 313K and 333K. Besides that, the value of self diffusion at 313K and 333K for HMDA and CO2 are (7.585E-07 m2/s, 2.5475E-06 m2 /s) and (7.6495E-07 m2/s, 2.7542E-06 m2/s) respectively. Based on the result, it found that the temperature 333K show higher result for intermolecular interaction and self diffusion coefficient compared to temperature 313K. It can be seen that, the result of this simulation is obey the theory which is as the temperature increase, the self diffusion coefficient and the g(r) value for intermolecular interaction also higher.